The Effectiveness of Situation-Based Learning Model on Mathematics Learning Outcomes: A Quasi-Experimental Study - Nor Amalliyah (Jurnal Inovasi Matematika, 2026)
Mathematics learning needs to be designed optimally to develop students' various mathematical skills, including the capacity to understand concepts, mathematical communication, connecting concepts with each other, logical reasoning, and mathematical problem solving. Student success cannot be separated from their learning experiences. A teacher is required to determine the right teaching strategy according to the content of the material to be taught. In this context, Situation-Based Learning (SBL) is a worthy alternative to consider. This research aims to identify the effectiveness of Situation-Based Learning in improving student learning outcomes. The research approach uses a quasi-experimental design with a non-equivalent control group involving grade students from Bustanul Hikmah Islamic Junior High School, Lamongan, who were randomly divided into two classes: the experimental group ( ) and the control group ( ). The effectiveness of Situation-Based Learning implementation is measured through quantitative data analysis using observation instruments and learning achievement tests. Data analysis techniques include descriptive statistics, assumption tests (Shapiro-Wilk and Levene), independent t-tests, and N-Gain to assess learning effectiveness. The findings show that implementing the Situation-Based Learning model has proven effective in improving student learning outcomes. The use of this learning model can foster student motivation throughout the learning process.